Introduction to the Issue: "Promoting Children’s Participation in Research, Policy and Practice" - Aldridge, Jo ca. 20./21. Jh. (Social Inclusion, 2017)
It is more than twenty years since the United Nations Convention on the Rights of the Child gave governments and states an international mandate to ensure the safety and wellbeing of children and young people and to promote their participation in decisions that affect their lives. Considerable advances have been made since that time that have, in some but not all instances, seen transformations in the status, roles and responsibilities of children and young people and in the ways in which they are perceived and treated. These advances have included greater inclusion of children’s voices in research, policy and practice underpinned by children’s rights to participation and ‘best interests of the child’ decision-making. Bringing together a unique collection of international articles from authors with considerable expertise in researching and working with children and young people, this thematic issue explores some of the ways in which facilitating constructive dialogues with children and young people, and engaging them more directly in consultation about their lives, has led to genuine improvements in the way they are treated and understood. It also considers some of the barriers that exist to prevent children and young people from full participation in public life, some of which occur as a result of structural or systemic factors, while others are the result of the decisions adults make on their behalf.